Labour Market Institutions and Inflation Differentials in the EU - Gaetano D'Adamo; Riccardo Rovelli (Institute for the Study of Labor (IZA), 2015)
Adopting a simple Phillips curve framework, we show that different labour market institutions across EU countries are associated with significant differences in the response of inflation to unemployment and exchange rate shocks. More wage coordination and higher union density flatten the Phillips curve and increase the inflation response to the real exchange rate, i.e. the exchange rate pass-through. In addition, using a new approach to the classification of goods and services as "traded" or "non-traded", we show that both these institutional effects are significantly stronger for the more exposed (traded) sector.
Keywords: E31; J50; J60; 330; sectoral inflation differentials; inflation determinants; labour market institutions; EU 27